Digitalisasi Edukasi Gizi Remaja sebagai Strategi Pencegahan Stunting dan Diabetes Melitus di Kalisat - Susilawati, Susilawati; Sugijati, Sugijati (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
Adolescents are a strategic age group in developing long-term healthy nutritional behaviors. However, the 2023 Indonesian Health Survey showed an increase in the prevalence of adolescents at risk of diabetes mellitus (DM) of up to 2.9%, while the stunting rate in Jember Regency remained at 25.4%. This situation highlights the need for innovative nutrition education that is engaging and accessible to adolescents. This community service activity aims to improve adolescent nutrition knowledge through digitalization of education as an early prevention strategy for stunting and DM. The program was implemented in Glagahwero Village, Kalisat District, involving 23 adolescent boys and girls. The methods used included creating short videos, infographics, and educational e-booklets, as well as evaluating knowledge through pre- and post-tests. Results showed an average increase in scores from 87.82% to 93.91% after the intervention. 100% of participants stated that TikTok was the most engaging and effective medium for understanding nutrition messages. Digitalization of nutrition education has been proven to improve nutritional literacy and adolescent awareness of stunting and DM prevention. This program is expected to become a model for technology-based health education at the community level.